Performance, egg quality and serum biochemical parameters of laying hens fed corn distillers' grains with soluble diets with or without probiotic supplementation - Nadya MINCHEVA; Pavlina HRISTAKIEVA; Ivelina IVANOVA; Magdalena OBLAKOVA; Krasimir VELIKOV; Nikolay IVANOV; Ivan SLAVOV (Journal of Central European Agriculture)
This study investigated the effects of feeding corn distillers' dried grains with solubles (corn DDGS) with or without probiotic supplementation on performance, egg quality and serum biochemical parameters of laying hens aged 22 to 33 weeks. A total of 240 brown-egg laying hens (RIR × RIW) were allocated to four dietary treatments in a 2 × 2 factorial design, with two levels of DDGS (0% and 15%) and two levels of probiotic (0% and 0.05% B-act®). Hens fed diets containing 15% DDGS showed reduced feed intake by 3.22%, final body weight by 2.91%, average egg weight by 2.34% and egg mass output by 9.67% compared to those fed 0% DDGS (P<0.05). The inclusion of DDGS significantly (P<0.05) improved internal egg quality by increasing Haugh units and yolk yellowness (b*), while probiotic supplementation influenced yolk colour parameters L* (lightness) and b* (yellowness). Although probiotics alone did not affect (P>0.05) laying performance, their combination with DDGS significantly improved eggshell thickness and yolk pigmentation at 32 weeks of age (P<0.05). Serum parameters were unaffected by DDGS and/or probiotic (P>0.05), except for a synergistic interaction that increased serum albumin levels in hens receiving both (P<0.05). These findings indicate that the addition of 15% DDGS enhances egg quality but may negatively affect overall performancе. Probiotic supplementation complements DDGS by improving eggshell and yolk quality. Further research is needed to optimise the use of DDGS and probiotics in laying hen diets to maximise productivity.